Virome Sequencing in Patients With Myocarditis. (July 2020) - Heidecker, Bettina; Williams, Simon H.; Jain, Komal; Oleynik, Alexandra; Patriki, Dimitri; Kottwitz, Jan; Berg, Jan; Garcia, Joel A.; Baltensperger, Nora; Lovrinovic, Marina; Baltensweiler, Andrea; Mishra, Nishay; et al.
Abstract : Background: Polymerase chain reaction analyses of cardiac tissues have detected viral sequences in up to 67% of cases of myocarditis. However, viruses have not been implicated in giant cell myocarditis (GCM). Furthermore, efforts to detect viruses implicated in myocarditis have been unsuccessful in more accessible samples such as peripheral blood. Methods: We used Virome Capture Sequencing for Vertbrate Viruses (VirCapSeq-VERT), a method that simultaneously screens for all known vertebrate viruses, to investigate viruses in 33 patients with myocarditis. We investigated peripheral blood mononuclear cells (n=24), plasma (n=27), endomyocardial biopsies (n=2), and cardiac tissue samples from explanted hearts (n=13). Results: Nine patients (27%) had GCM and 4 patients (13%) had fulminant myocarditis. We found the following viruses in the blood of patients with myocarditis: Epstein Barr virus (n=11, 41%), human pegivirus (n=1, 4%), human endogenous retrovirus K (n=27, 100%), and anellovirus (n=15, 56%). All tissue samples from fulminant myocarditis (n=2) and GCM (n=13) contained human endogenous retrovirus K. Conclusions: No nucleic acids from viruses previously implicated in myocarditis or other human illnesses were detected in relevant amounts in cardiac tissue samples from GCM or in blood samples from other types of myocarditis. These findings do not exclude a role for viral infection in GCM but do suggest that if viruses are implicated, the mechanism is likely to be indirect rather than due to cytotoxic infection of myocardium. Abstract : Supplemental Digital Content is available in the text.